The impact of “Digital–Green” integration on urban green transformation performance - Zheng, Lin Lin; Suo, Lei; Yu, Weiming; Zhang, Jingyang (Frontiers in Environmental Science, 2026)
As nations increasingly align digital and sustainable development goals, this study empirically investigates the impact of Digital–Green Integration (DGI) on Urban Green Transformation Performance (UGTP) using panel data from 283 Chinese cities (2011–2023). Based on a "government–market–society" framework and spatial econometric models, the findings reveal that DGI currently exerts a significant negative impact on UGTP, although this adverse effect weakens over the long term. Mechanism analysis highlights a complex interaction: while economic agglomeration exacerbates the negative impact, factors such as environmental protection governance, financial development, and the public service environment effectively mitigate it. Notably, public environmental consciousness shifts from intensifying adverse effects in the short term to suppressing them over time. Spatially, DGI exhibits a "Central rise, East-West divergence" pattern, characterized by negative spillovers within a 760 km threshold and positive spillovers between 760–900 km. By elucidating these transmission mechanisms and defining spatial spillover boundaries, this study enriches the theoretical understanding of DGI and offers critical insights for designing region-specific policies to overcome transformation bottlenecks.